Peran Label Halal pada Pembelian Air Minum dalam Kemasan: Perspektif Manajemen Bisnis Syariah - Hatapayo, Siti Nur F.; Karnudu, Fitria; Hamizar, Arizal (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2024)
The research aims to determine the role of the halal label in purchasing decisions for Ayudes Packaged Drinking Water (AMDK) products in Ambon City and what the role of the halal label is in reviewing sharia business management. This research was carried out in the Ambon City community and at the Ayudes AMDK company using qualitative methods. The data collection techniques used were observation, interviews, and documentation with a number of informants who were directly involved in the research. The results of this research show that the decision to purchase Ayudes bottled drinking water in Ambon City based on the role of the halal label shows that consumers do not pay attention to the inclusion of a halal label on the product packaging and pay more attention to the quality and location of the bottled water factory.